Traveling with an eating disorder - Ramanayake, Uditha; Wengel, Yana (Frontiers in sustainable tourism, 2024)
This study aims to uncover what it means to be a tourist with an invisible impairment. We highlight this important yet neglected area within inclusive and accessible tourism by examining how eating disorders impact travel. The subject of eating disorders in the context of travel is not well-articulated, and academic attention toward eating disorders is scant. To explore the lived experiences of an eating disorder and travel, we adopted qualitative research methods. Our phenomenological study followed the purposeful sampling technique and conducted in-depth interviews to collect data. Since research on this neglected traveler population is at an early stage, this research contributes to a fruitful future for this research area by exploring eating disorders and their impact on travel under the key themes of lacking public social awareness, change of routine and structure, responsibility, and access to support and barriers of the skin. The findings expand scant research into traveling with an eating disorder. Importantly, this study reveals the imbalance between what is visible externally vs. the real lived experience and advocates for diversity and inclusion in the context of travel. This research calls for closer dialogue between researchers, society, and people with eating disorders, such as our participants with an eating disorder, to ensure that the value of their voices is highlighted and heard by the stakeholders of the tourism industry. The findings of this research will be helpful in fostering tourism stakeholders' ability to provide service and care for people with eating disorders and other invisible disabilities.